2018
DOI: 10.1177/1098300718768208
|View full text |Cite
|
Sign up to set email alerts
|

A Quasi-Experimental Design Analysis of the Effects of School-Wide Positive Behavior Interventions and Supports on Discipline in Florida

Abstract: During the 2011-2012 school year, almost 3.4 million elementary and secondary students in the United states received at least one in-school suspension (ISS), whereas 3.1 million received at least one out-of-school suspension (OSS; Snyder, de Brey, & Dillow, 2016). Nearly one quarter of a million students engaged in behaviors that resulted in referrals to law enforcement, and more than 64,000 students were arrested for acts that occurred on school grounds or during off-campus school activities such as transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 43 publications
5
47
0
Order By: Relevance
“…Sixteen studies reporting outcomes in the behavior domain included suspensions (ISS and OSS) and nine studies included ODRs. Other behaviors outcomes included corporal punishment, expulsion, referral to law enforcement, school‐related arrest (e.g., Gage, Grasley‐Boy, Peshak George, Childs, & Kincaid, ; Grasley‐Boy et al, ), bullying and peer rejection (Gage, Rose et al ; Waasdorp et al, ), and emotional disturbance eligibility (Porter, ). Most studies reported proportions of students with a behavior outcome (e.g., OSS), while two studies used the TOCA‐checklist (TOCA‐C; Koth, Bradshaw, & Leaf, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen studies reporting outcomes in the behavior domain included suspensions (ISS and OSS) and nine studies included ODRs. Other behaviors outcomes included corporal punishment, expulsion, referral to law enforcement, school‐related arrest (e.g., Gage, Grasley‐Boy, Peshak George, Childs, & Kincaid, ; Grasley‐Boy et al, ), bullying and peer rejection (Gage, Rose et al ; Waasdorp et al, ), and emotional disturbance eligibility (Porter, ). Most studies reported proportions of students with a behavior outcome (e.g., OSS), while two studies used the TOCA‐checklist (TOCA‐C; Koth, Bradshaw, & Leaf, ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the current review found promising effects of SWPBIS across all three outcomes, only a few reported outcomes for specific population groups (e.g., minority students) or outcomes at the student level. Four studies (Gage, Grasley‐Boy, et al, ; Grasley‐Boy et al, ; Mozley, ; Porter, ) addressed differential effects of SWPBIS on particular groups of students, including students with disabilities (Gage, Grasley‐Boy et al, ), students identified for emotional disturbance (Porter, ), and African American students (Gage, Grasley‐Boy et al, ; Grasley‐Boy et al, ; Mozley, ). In particular, Gage, Grasley‐Boy et al () found significantly fewer OSS for students with disabilities and African American students in schools implementing SWPBIS compared with students in comparison schools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Gage, Lee, et al (2018) examined the impact of PBIS on suspensions in schools in Georgia and found significantly fewer in- and out-of-school suspensions for schools implementing PBIS with fidelity. The results for out-of-school suspensions have also been replicated in Florida (Gage, Grasley-Boy, et al, 2018) and in California (Grasley-Boy et al, 2019). It is also noteworthy that these studies found that schools implementing PBIS with fidelity had fewer out-of-school suspensions for vulnerable groups of students, including Black students and students with disabilities (see Gage, Grasley-Boy, et al, 2018).…”
Section: What Is the Evidence Base For Pbis And Suspensions?mentioning
confidence: 84%
“…Research indicates that implementing PBIS with fidelity can have a significant and meaningful impact on reducing suspensions (Gage, Grasley-Boy, et al, 2018; Gage, Lee, et al, 2018). Although no universal scale-up support program exists, schools in every state have access to some level of training support through partners with the OSEP Technical Assistance Center.…”
Section: Resultsmentioning
confidence: 99%